Local and systemic immunological response in feline chronic gingivostomatitis: a critical review - Lopes, Rafael S.; Carvalho, Pedro P.; Pires, Maria A.; Rodrigues-Santos, Paulo; Costa, Eduardo; Requicha, João F. (Frontiers in Immunology, 2025)
IntroductionA comprehensive understanding of the oral immune response in feline chronic gingivostomatitis (FCGS) is crucial for veterinarians to improve clinical and therapeutic decisions. This critical review addresses the local and systemic immune responses associated with FCGS.MethodsA comprehensive database search was conducted using the PubMed/MEDLINE database, resulting in 3,358 studies. Following a rigorous screening process, in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, 17 publications were included in this review.ResultsThe local immune response in FCGS is primarily evaluated through histopathological and immunohistochemical analyses of oral biopsy samples, and by analysis of saliva. Histopathological analysis reveals a dense lymphoplasmacytic infiltration within the mucosa, indicating chronic inflammation. Immunohistochemical staining identifies increased numbers of mast cells, altered expression of immunoglobulins (IgG, IgM, and IgA) and presence of immunomarkers (CD3+, CD4+, CD8+ T cells and Mott cells), indicating immune dysregulation. Systemic immune features of FCGS are investigated in blood samples through flow cytometry, polymerase chain reaction, and enzyme-linked immunosorbent assay. A consistent finding is an increased level of pro-inflammatory cytokines (IL-6, TNF-α, and IFN-γ), indicating intense systemic immune activation. Neutrophilia, disrupted CD4/CD8 T-cell ratio, a reduction in CD21+ B cells and alterations in regulatory T cells expressing FOXP3, suggests chronic immune regulation dysfunction.DiscussionThe findings highlight a complex relationship between local and systemic immune responses, by significant alterations in T cell subsets, pro-inflammatory cytokines, and immunoglobulin expression. The frequent presence of CD3+, CD4+, and CD8+ T cells, along with impaired regulatory T cell (FOXP3+) function, suggests that dysregulated cell-mediated immunity is a key factor in the pathogenesis of FCGS. Elevated systemic immunomarkers (IL-6, TNF-α, and IFN-γ), provide further evidence of a chronic immune activation state. The immunopathological similarities observed between FCGS and human oral lichen planus reinforce the potential of FCGS individuals as a spontaneous model for comparative research. This review found that there is a lack of comprehensive information on the oral immune response of FCGS. Further observational and experimental studies focusing on the link between local and systemic immune responses are essential to fully understand the complexity and guide the development of novel, evidence-based therapeutic strategies.